2020
DOI: 10.12681/mms.19490
|View full text |Cite
|
Sign up to set email alerts
|

Sea turtle strandings, sightings and accidental catch along the Croatian Adriatic coast

Abstract: The northern Adriatic Sea has long been known as the foraging and developmental habitat of loggerhead sea turtles. Previous literature on stranded, floating, sighted, and accidentally caught sea turtles is fragmentary and mainly obtained from this shallower northern part. This work presents data on 272 records of stranded, floating, sighted and accidentally captured turtles within the entire Croatian Adriatic. The data was collected through the national stranding network for strictly protected marine species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…It would be interesting to explore in greater detail such year-to-year variability once a more prolonged time series will become available, a step that will allow us to better understand sea turtles strandings in relation to parameters such as sea surface temperature, chlorophyll concentration and fishing effort, an approach recently exploited in the Adriatic Sea for fishery by-caught individuals (Pulcinella et al, 2019;Bonanomi et al, 2022). The number of stranded sea turtles•km -1 as well as absolute numbers of strandings during three years, clearly confirmed that the area south of the Po River delta is the most impacted in Italy (Casale et al, 2010) and perhaps in the whole Mediterranean Sea (Tomás et al, 2008;Türkozan et al, 2013;Belmahi et al, 2020;Hama et al, 2020;Dimitriadis et al, 2022). Indeed, it is important to highlight that monitoring activities spanned only about 18 km of coastline and the numbers presented herein represented underestimates as we are aware of other and partly overlapping monitoring programs for which data could not be accessed.…”
Section: Data Collectionmentioning
confidence: 61%
See 1 more Smart Citation
“…It would be interesting to explore in greater detail such year-to-year variability once a more prolonged time series will become available, a step that will allow us to better understand sea turtles strandings in relation to parameters such as sea surface temperature, chlorophyll concentration and fishing effort, an approach recently exploited in the Adriatic Sea for fishery by-caught individuals (Pulcinella et al, 2019;Bonanomi et al, 2022). The number of stranded sea turtles•km -1 as well as absolute numbers of strandings during three years, clearly confirmed that the area south of the Po River delta is the most impacted in Italy (Casale et al, 2010) and perhaps in the whole Mediterranean Sea (Tomás et al, 2008;Türkozan et al, 2013;Belmahi et al, 2020;Hama et al, 2020;Dimitriadis et al, 2022). Indeed, it is important to highlight that monitoring activities spanned only about 18 km of coastline and the numbers presented herein represented underestimates as we are aware of other and partly overlapping monitoring programs for which data could not be accessed.…”
Section: Data Collectionmentioning
confidence: 61%
“…The number of stranded sea turtles•km -1 as well as absolute numbers of strandings during three years, clearly confirmed that the area south of the Po River delta is the most impacted in Italy (Casale et al ., 2010) and perhaps in the whole Mediterranean Sea (Tomás et al ., 2008; Türkozan et al ., 2013; Belmahi et al ., 2020; Hama et al ., 2020; Dimitriadis et al ., 2022). Indeed, it is important to highlight that monitoring activities spanned only about 18 km of coastline and the numbers presented herein represented underestimates as we are aware of other and partly overlapping monitoring programs for which data could not be accessed.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from industrial fisheries bycatch include green turtles, leatherbacks, loggerheads and olive ridleys (IMROP, 2020), while artisanal fisheries primarily catch green turtles and the occasional leatherback (Wolff et al, 1993; Mint Hama, Fretey & Aksissou, 2013; Fretey & Mint Hama, 2014). A single mention of a stranded hawksbill is found in the literature from the last two decades (Hama et al, 2019); however, local coastal fishers interviewed by Mint Hama, Fretey & Aksissou (2013) between 2009 and 2011 recognized the hawksbill as one of four species encountered along the coast, along with green turtles, loggerheads and leatherbacks.…”
Section: Resultsmentioning
confidence: 99%
“…From 2009 to 2016, Hama et al (2019) retrieved 1,787 stranded carcasses, of which 1,654 were green turtles. Four of these were found entangled in fishing nets or ropes/lines, 10 others presented flipper and neck injuries of unspecified cause and eight had been killed for consumption in fishing villages or camps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation